2 John Ray, Digest of the Statutes of the State of Louisiana 190 (1870) - (:unkn) unknown (My University, 1870)
37: A soldier, who unnecessarily or without order from a superior officer, comes to any parade with his musket, rifle or pistol loaded with ball, slug or shot, or so loads the same while on parade, or unnecessarily or without order from a superior officer, discharges the same when going to, returning from, or upon parade, shall forfeit not less than five nor more than twenty dollars, to be recovered before any court of competent jurisdiction upon complaint of the clerk, one-half to his use and one-half to the use of the Commanding officer.
Keywords: ARMED FORCES